2016
DOI: 10.1177/1753193416629070
|View full text |Cite
|
Sign up to set email alerts
|

Model-based roentgen stereophotogrammetric analysis of the surface replacement trapeziometacarpal total joint arthroplasty

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…2015, Ten Brinke et al. 2016). No articles concerning the radiocarpal, distal radioulnar, metacarpophalangeal, or interphalangeal joints were found (Table 3, see Supplementary data).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2015, Ten Brinke et al. 2016). No articles concerning the radiocarpal, distal radioulnar, metacarpophalangeal, or interphalangeal joints were found (Table 3, see Supplementary data).…”
Section: Resultsmentioning
confidence: 99%
“…The small size of the surrounding bone, especially in the trapezium bone, and the small number of markers that can be inserted around the prosthesis might lead to over-projection of the prosthesis over the markers and to a lack of detectable markers (Ten Brinke et al. 2016). On the other hand, a cadaver study by Ooms et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the 46 total implant arthroplasty articles (excluding silastic replacements) published between 2000 and 2019 (Apard and Saint-Cast, 2007; Badia and Sambandam, 2006; Brikout and Rezzouk, 2016; Brutus and Kinnen, 2004; Caekebeke and Duerinckx, 2018; Cebrian-Gomez et al., 2019; Chug et al., 2014; Cootjans et al., 2017; Craik et al., 2017; De Smet et al., 2004; Dehl et al., 2017; Dreant and Poumellec, 2019; Erne et al., 2018; Goubau et al., 2013; Guardia et al., 2010; Hansen and Vainorius, 2008; Hernández-Cortés et al., 2012; Isselin, 2001; Jacoulet, 2005; Jager et al., 2013; Johnston et al., 2012; Kaszap and Daecke, 2012; Klahn et al., 2012; Kollig et al., 2017; Krukhaug et al., 2014; Lemoine et al., 2009; Maes et al., 2010; Martin-Ferrero, 2014; Masmejean et al., 2003; Moutet et al., 2001; Pendse et al., 2009; Pérez-Ubeda et al. 2003; Regnard, 2006; Robles-Molina et al., 2017; Schuhl, 2001; Semere et al., 2015; Seng and Chantelot, 2013; Spaans et al., 2016; ten Brinke et al., 2016; Thillerman et al., 2016; Toffoli and Teissier, 2017; Ulrich-Vinther et al., 2008; Vander Eecken et al., 2012; van Rijn and Gosens, 2010; Vissers et al., 2019; Zollinger et al., 2008) functional scores were used infrequently (Table 1). Of the 30 articles published in the last 10 years (2010–2019), the use of functional scores has increased but are still used in fewer than 50% of the studies.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Previously, our group presented the 5-year results of a radiostereometric analysis (RSA) of the Surface Replacement (SR) TMC joint prosthesis (SR™TMC, Avanta®, San Diego, CA) [6]. This study showed a survival of eight out of ten prostheses with satisfying clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The experience with RSA in the TMC joint is limited: two experimental and two small clinical studies have been published up to now [6][7][8][9]. These studies have learned us that RSA of the TMC joint is feasible with high precision for translations, but precision for rotation measurement is poor.…”
Section: Introductionmentioning
confidence: 99%